Pharmaceuticals Licensing and Reimbursement in the European Union, United States, and Japan. Issue 6 (17th October 2016) - Oye, KA; Eichler, HG; Hoos, A; Mori, Y; Mullin, TM; Pearson, M
Abstract : This article describes recent developments in licensing and reimbursement policies in the EU, US, and Japan, examines causes of changes and compares differences and projects trends. With respect to licensing, the European Medicines Agency (EMA), US Food and Drug Administration (FDA), and Japan's Pharmaceuticals and Medical Devices Agency (PMDA) are committed to rigorous evaluation of pharmaceuticals in advance of market access with feedback from postmarket experience. The EMA is exploring integrated adaptive pathways for licensing, with formal pilot tests to provide a practical proof of concept. The FDA is augmenting traditional licensing procedures through reforms including Breakthrough Product Designation. The PMDA is implementing reforms to foster innovation and earlier patient access through its Sakigake strategy and licensing reforms on regenerative medicines. With respect to reimbursement, several generalizations emerge. Relative to US counterparts, EU payers typically set higher standards for evidence of effectiveness as a condition of reimbursement, impose tougher limits on reimbursement by indication, and drive harder deals in negotiations over prices.